2010
DOI: 10.1007/s10096-010-1026-8
|View full text |Cite
|
Sign up to set email alerts
|

Crucial epitopes of Wuchereria bancrofti abundant larval transcript recognized in natural infection

Abstract: Lymphatic filariasis is a tropical disease, with over 40 million people seriously incapacitated due to lymphangitis and elephantiasis. Over 99% of infections are caused by the nematode Wuchereria bancrofti. Expressed sequence tag (EST) analysis of filarial genome identified novel infective larval (L3) stage-specific antigen, abundant larval transcript (ALT-2), which was shown to be highly essential for parasite establishment and survival in the host. The unique structural features and immunological characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 19 publications
3
14
0
Order By: Relevance
“…Among them, the antibody level was significantly ( P < 0.0001) high for the epitope regions TRX P1 & TRX P2 , followed by ALT‐2 P1, P7 and P8. ALT‐2 P2 and P3 showed significant ( P < 0.05) levels of antibody response except TGA P1 which confirms the peptides contain immunodominant B epitopes reported earlier . The antisera of TGA P1 did not show significant reactivity with its corresponding epitope in FEP.…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…Among them, the antibody level was significantly ( P < 0.0001) high for the epitope regions TRX P1 & TRX P2 , followed by ALT‐2 P1, P7 and P8. ALT‐2 P2 and P3 showed significant ( P < 0.05) levels of antibody response except TGA P1 which confirms the peptides contain immunodominant B epitopes reported earlier . The antisera of TGA P1 did not show significant reactivity with its corresponding epitope in FEP.…”
Section: Resultssupporting
confidence: 83%
“…The reactivity of FEP with peptide {PC1 (TRX P1 –TRX P2 , conjugate), TGA P1, ALT P1, P2, P3, P7 and P8 which have been screened in previous study and antisera were raised for the same in mice} antisera was carried out to check whether antipeptide antibodies were capable of recognizing the epitopes present in the whole protein (FEP) by ELISA. The results showed that antibodies induced by individual peptides were recognized by epitopes of FEP indicating the presence of corresponding peptide regions in the chimeric protein (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations